Impact of sleep disorders in Japanese patients with functional dyspepsia (FD): Nizatidine improves clinical symptoms, gastric emptying and sleep disorders in FD patients. Issue 8 (22nd July 2013) - Futagami, Seiji; Yamawaki, Hiroshi; Izumi, Nikki; Shimpuku, Mayumi; Kodaka, Yasuhiro; Wakabayashi, Taiga; Nagoya, Hiroyuki; Shindo, Tomotaka; Kawagoe, Tetsuro; Gudis, Katya; Itoh, Takashi; Sakamoto, Choitsu
Abstract Background and Aims The association between functional dyspepsia (FD) and sleep disorders has yet to be studied in detail. The aim of this study is to evaluate the risk factors associated with sleep disorders and the clinical response to nizatidine therapy for sleep disorders in Rome III‐based FD patients. Methods We enrolled 94 FD patients and 52 healthy volunteers. We used Rome III criteria to evaluate upper abdominal symptoms, and the Self‐Rating Questionnaire for Depression scores to determine depression status. Sleep disorder was evaluated using Pittsburgh Sleep Quality Index (PSQI) scores, and degree of anxiety by the State‐Trait Anxiety Inventory. Gastric motility was evaluated. Thirty‐four FD patients were treated with nizatidine (300 mg/day) or placebo for 4 weeks in a crossover trial. The primary end point of this study was to determine whether nizatidine could improve clinical symptoms and sleep disorders in FD patients. Results The global PSQI score for FD patients was significantly (P < 0.001) higher compared with healthy volunteers. There were significant correlations between global PSQI scores and total Gastrointestinal Symptom Rating Scale and Self‐Rating Questionnaire for Depression scores (P < 0.001, P < 0.0001, respectively) in FD patients than in healthy volunteers. We found significant relationships between subjective sleep quality and both Tmax and T1/2 values in FD patients. Nizatidine significantly improved certain clinical symptoms, gastric emptying, and global PSQI score compared with placebo treatment. Conclusion Sleep disorders in FD patients correlated significantly with both clinical symptoms of dyspepsia and depression compared with healthy volunteers. Nizatidine significantly improved gastroesophageal reflux symptoms, gastric emptying, and sleep disorders in FD patients.